2023
DOI: 10.1002/ptr.8037
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin supplementation impact on insulin resistance, lipid profile, blood pressure, and oxidative stress in polycystic ovary syndrome patients: A triple‐blind randomized clinical trial

Masoome Jabarpour,
Ashraf Aleyasin,
Maryam Shabani Nashtaei
et al.

Abstract: Astaxanthin (ASX) is a natural carotenoid compound found in several of microorganisms and seafood. It may have numerous therapeutic benefits for polycystic ovarian syndrome (PCOS) patients. The aim of this study was to investigate the effect of ASX on lipid profile, insulin resistance (IR), blood pressure (BP), and oxidative stress (OS) levels in infertile PCOS patients. Overall, 58 infertile women with diagnosed PCOS participated in this triple‐blind randomized clinical trial. They were randomly assigned to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…[38][39][40] Meanwhile, recent research from our lab suggested that ASX may be able to influence ER stress and OS in the granulosa cells of PCOS patients. 41 As OS induces ER stress and plays a pivotal role in the pathogenesis of PCOS, and also considering the interactions between ER stress, inflammation, OS and apoptosis, in this study, we examined the effect of ASX on serum inflammatory markers, active caspase levels and gene expression related to ER stress-apoptosis in PBMC of women with PCOS. Furthermore, we evaluated the efficacy of ASX on disease symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] Meanwhile, recent research from our lab suggested that ASX may be able to influence ER stress and OS in the granulosa cells of PCOS patients. 41 As OS induces ER stress and plays a pivotal role in the pathogenesis of PCOS, and also considering the interactions between ER stress, inflammation, OS and apoptosis, in this study, we examined the effect of ASX on serum inflammatory markers, active caspase levels and gene expression related to ER stress-apoptosis in PBMC of women with PCOS. Furthermore, we evaluated the efficacy of ASX on disease symptoms.…”
Section: Introductionmentioning
confidence: 99%